Development of soft‐sphere contact models for thermal heat conduction in granular flows. Issue 12 (8th June 2016) - Morris, A. B.; Pannala, S.; Ma, Z.; Hrenya, C. M.
Abstract : Conductive heat transfer to flowing particles occurs when two particles (or a particle and wall) come into contact. The direct conduction between the two bodies depends on the collision dynamics, namely the size of the contact area and the duration of contact. For soft‐sphere discrete‐particle simulations, it is computationally expensive to resolve the true collision time because doing so would require a restrictively small numerical time step. To improve the computational speed, it is common to increase the "softness" of the material to artificially increase the collision time, but doing so affects the heat transfer. In this work, two physically‐based correction terms are derived to compensate for the increased contact area and time stemming from artificial particle softening. By including both correction terms, the impact that artificial softening has on the conductive heat transfer is removed, thus enabling simulations at greatly reduced computational times without sacrificing physical accuracy. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4526–4535, 2016